2021
DOI: 10.1016/j.mbplus.2021.100085
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of type VIII collagen reduces blood pressure, increases carotid artery functional distensibility and promotes elastin deposition

Abstract: Highlights The matrix protein collagen VIII influences conduit artery compliance. Collagen VIII negatively regulates elastin. Collagen VIII KO increases elastin synthesis and content in carotid arteries. Collagen VIII and elastin exert opposing regulation of smooth muscle cell phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…For Surti, the genes exactly overlapped with that of the Bhadawari breed. Among the reported genes, Collagen VIII ( COL8 ) is reported to play a major role in vascular integrity [ 68 ]. Jaffarabadi carried the longest CNVR on chromosome 14, which was the smallest one among all the breeds (0.246 Mb) contributing only 0.0089% of the genomic size.…”
Section: Resultsmentioning
confidence: 99%
“…For Surti, the genes exactly overlapped with that of the Bhadawari breed. Among the reported genes, Collagen VIII ( COL8 ) is reported to play a major role in vascular integrity [ 68 ]. Jaffarabadi carried the longest CNVR on chromosome 14, which was the smallest one among all the breeds (0.246 Mb) contributing only 0.0089% of the genomic size.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested that in acute LHF of mice, Col 8 promotes myofibroblast differentiation and fibrosis and protects from early mortality and LV dilatation in response to pressure overload (Skrbic et al, 2015). In a recent study, mice lacking Col8 had reduced baseline blood pressure and altered ECM composition of carotid arteries, suggesting that Col 8 negatively regulates elastic fiber formation in the ECM matrix of blood vessels (Mohabeer et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…Regarding non-fibrillar collagens, the type VIII subunit (included in the subfamily of network-forming collagens) participates in cardiogenesis, while reduced expression is reported in physiological adult myocardium. In cardiovascular diseases, type VIII collagen has been implicated in cardiac dilatation-derived heart failure following pressure overload [ 24 ], carotid artery distensibility [ 25 ], and atrial fibrillation [ 26 ]. In fact, fibroblasts isolated from col8-knock-out mice displayed lower expression of transforming growth factor-β and α-smooth muscle actin, key players in post-MI cardiac fibrosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%